Survival Mechanisms in antarctic Lakes - Laybourn-Parry, J (2002)
In Antarctic lakes, organisms are confronted by continuous low temperatures as well as a poor light climate and nutrient limitation. Such extreme environments support truncated food webs with no fish, few metazoans and a dominance of microbial plankton. The key to success lies in entering the short Antarctic summer with actively growing populations. In many cases, the most successful organisms continue to function throughout the year. The few crustacean zooplankton remain active in the winter months, surviving on endogenous energy reserves and, in some cases, continuing development. Among the Protozoa, mixotrophy is an important nutritional strategy. In the extreme lakes of the McMurdo Dry Valleys, planktonic cryptophytes are forced to sustain a mixotrophic strategy and cannot survive by photosynthesis alone. The dependence on ingesting bacteria varies seasonally and with depth in the water column. In the Vestfold Hills, Pyramimonas, which dominates the plankton of some of the saline lakes, also resorts to mixotrophy, but does become entirely photosynthetic at mid-summer. Mixotrophic ciliates are also common and the entirely photosynthetic ciliate Mesodinium rubrum has a widespread distribution in the saline lakes of the Vestfold Hills, where it attains high concentrations. Bacteria continue to grow all year, showing cycles that appear to be related to the availability of dissolved organic carbon. In saline lakes, bacteria experience sub-zero temperatures for long periods of the year and have developed biochemical adaptations that include anti-freeze proteins, changes in the concentrations of polyunsaturated fatty acids in their membranes and suites of low-temperature enzymes.